The hypothesis of a postpositional compensatory lengthening (so-called van Wijk’s law) vs. the relative chronology of Common Slavic phonological developments – in search of inconsistencies - Babik, Zbigniew (Baltistica, 2017)
“Van Wijk’s law” is currently defined by its advocates as a lengthening of short or shortened medial and final vowels due to an assimilation of the postconsonantal *j to them. In the present paper I am trying to demonstrate that this assumption is at variance with the relative chronology of Slavic, according to which the loss of yod after liquids and nasals must be dated before the rise of new timbre distinctions and before the shortening of final long vowels.